35 Does australian-modified karnofsky performance status (akps) help predict outcome for patients admitted to a hospice inpatient unit?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hayes, Jennifer
Abstract : Background: Australian-modified Karnofsky Performance Status (AKPS) is recommended as part of the OACC (Outcomes And Complexity Collaborative) suite of measures to assess palliative patients' functional ability in 3 dimensions: activity, work and self-care. AKPS ranges from 100% (normal function) to 0% (dead). There are studies suggestive that Karnofsky Performance Status (not Australian-modified) may be predictive of survival. If AKPS on admission to a short-stay hospice inpatient unit (IPU) is related to the likelihood of the patient dying during that admission, this information may help with prognostication, discussions with patients and families, resource allocation and service development. Methods: A retrospective patient records review was conducted for all patients admitted to our hospice IPU over one year from 01.06.2016–31.05.2017. Results: There were a total 314 hospice admissions, and 305 patient records contained sufficient data for inclusion in the analysis. AKPS on admission ranged from 10% to 80%. There was a strong negative correlation between higher AKPS on admission and likelihood of dying during the admission (Pearson's Correlation Coefficient r=−0.9771, 95% CI: −0.87 to −0.99), and a strong positive correlation between higher AKPS and likelihood of discharge home (r=+0.9806). 92% of patients with AKPS=30% on admission subsequently died while still an inpatient, and 83% of patients with AKPS 50% survived to discharge. Discussion: This review suggests a strong association between AKPS on admission to our short-stay hospice and the outcome; in particular, patients with AKPS 30% or less are very likely to die during that admission. This knowledge may help to inform the support and information we offer to patients and families before and during hospice admission, as well as influencing how we allocate resources and plan future service developments.